Is the Therapeutic Mechanism of Repetitive Transcranial Magnetic Stimulation in Cognitive Dysfunctions of Depression Related to the Neuroinflammatory Processes in Depression? - Tateishi, Hiroshi; Mizoguchi, Yoshito; Monji, Akira (Frontiers in Psychiatry, 2022)
The lifetime prevalence of depression is reported to be more than 10 % and it is an important illness that causes various disabilities over a long period of life. The process of neuroinflammation is often reported to be closely linked to the pathophysiology of depression. About one-third of depression is known to be treatment-resistant depression (TRD), symptoms of which do not improve with adequate treatments. Cognitive dysfunction is one of the most important symptoms of depression that impedes rehabilitation of patients with depression. Repetitive transcranial magnetic stimulation (rTMS) is a minimally invasive and effective treatment of TRD and it is also known to be effective in cognitive dysfunctions in depression. Because the details of the therapeutic mechanism of rTMS are still unknown, we have been conducting studies to clarify the therapeutic mechanism of rTMS, especially focusing on cognitive dysfunctions in depression. In the present review, we will present our latest results and discuss them from the standpoint of neuroinflammation hypothesis of depression, while citing relevant literatures.